2021
DOI: 10.1126/sciimmunol.abj8825
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint blockade sensitivity and progression-free survival associates with baseline CD8 + T cell clone size and cytotoxicity

Abstract: The cytotoxicity and clone size of CD8 + T cell pretreatment are prognostic for immune checkpoint blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 59 publications
6
61
0
Order By: Relevance
“…De novo arthralgia, inflammatory arthritis, tendinitis/tenosynovitis, enthesitis and (poly-)myalgia have been reported in about 20% of ICI patients in clinical trials, with a large variation in prevalence due to differing criteria and awareness of these side effects 4 5. Intriguingly, the development of ICI-induced irAE has been associated with a better survival and clinical outcome,6–8 including patients with rheumatic irAEs 9–11. However, severe irAEs may force clinicians to terminate ICI therapy due to ICI-irAE-associated mortality for 0.5%–1.5% of patients 12.…”
Section: Introductionmentioning
confidence: 99%
“…De novo arthralgia, inflammatory arthritis, tendinitis/tenosynovitis, enthesitis and (poly-)myalgia have been reported in about 20% of ICI patients in clinical trials, with a large variation in prevalence due to differing criteria and awareness of these side effects 4 5. Intriguingly, the development of ICI-induced irAE has been associated with a better survival and clinical outcome,6–8 including patients with rheumatic irAEs 9–11. However, severe irAEs may force clinicians to terminate ICI therapy due to ICI-irAE-associated mortality for 0.5%–1.5% of patients 12.…”
Section: Introductionmentioning
confidence: 99%
“…This population shared a strong cytotoxic profile that mirrors those seen in clonally expanded peripheral blood CD8 populations in metastatic melanoma 18 . The clonal populations were largest in the three responding patients in our cohort and clonal size of expanded CD8+ T-cell clones has been shown to predict response to immune checkpoint blockade in metastatic melanoma 18,47 .…”
Section: Discussionmentioning
confidence: 63%
“…A recent study in humans used paired scRNA seq and scTCR seq to analyze CD4 + T cells and CD8 + T cells across 21 cancer types (including melanoma and breast, gastric, pancreatic, kidney, and esophageal cancers) from 316 patients; the study identified two major developmental trajectories that contributed to T cell exhaustion across multiple tumor types, based on transcriptional information [32]. Additionally, scTCR seq has been useful to inform mechanisms of response following PD-1-based immunotherapy in cancer patients [30,[36][37][38][39][40][41], as later discussed. While these studies have shown that scTCR seq data can be promising for focused analyses on T cell populations of interest, there are limitations to this method (Boxes 1-3).…”
Section: Trends In Immunologymentioning
confidence: 99%